The Effects of University Leadership Management: Efforts to Improve the Education Quality of State Institute for Islamic Studies (IAIN) of Bengkulu - Khairiah; Sirajuddin (Jurnal Pendidikan Islam, 2018)
The study of the paper aims to describe efforts to improve the quality of an institution's University of leadership management. The method uses a quantitative approach and path analysis. The point management institution is the academic education quality and the reputation of the university's publications which is the Tridarma statute for Higher Education in teaching-learning, research approach, and community service. Scientific publications are a starting point for global involvement in Higher Education management. Higher education management shows from Webometrics as an international recognition database for university rankings. It sees on the accreditation institutions such as ISO, National Accreditation for Higher Education as a quality service assessment bodies for Higher Education, e-Journal as a scientific publication agency in the publishing management network for papers written by lecturers and research findings of universities, and International office as an institution for national and international partnerships to achieve organizational success. The paper discusses 4 official Leadership Management Programs to improve the quality of the Bengkulu State Islamic Institute (IAIN Bengkulu).